Comparative Analysis of High Speed and Area Efficient Full-Adder using CMOS and MGDI Techniques - Pwint, Hnin Ngwe Yee; Hla, Tin Tin (The Indonesian Journal of Computer Science, 2024)
Extremely quick processing is crucial for very large-scale integrated (VLSI) circuits in the arithmetic logic unit. Complementary metal oxide semiconductor (CMOS) and modified gate diffusion input (MGDI) are beneficial technologies for designing high-speed circuits with better reliability and performance with regard to area and power consumption. This research work provides a comparative performance analysis of a full adder that is implemented with CMOS and MGDI technology. This work aims to develop a CMOS-based full-adder and a MGDI-based full-adder circuit for area-efficient and high-speed applications. First, the analysis and implementation of the XOR and NAND logic gates are designed using CMOS technology and the MGDI technique to create a full-adder design. The comparative analysis of integrated circuits in CMOS and MGDI technologies is primarily determined by the number of transistors and delay time. The full-adder is designed and analyzed using 90 nm technology, with performance characteristics evaluated using Cadence Virtuoso Tools.